History and modernity of Ukrainian-Polish relations during the second half of XIV century untill the beginning of XXI century (historical and legal aspects) - Honak, Ihor (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The historical aspects of Ukrainian-Polish relations and their influence on the modern tendencies of geopolitical relations of Ukraine and the Republic of Poland are analyzed. The consequences of the influence of «anti-Ukrainian» legislation on the inter-state Polish-Ukrainian relations were worked out. Proposed changes to Ukrainian legislation designed to neutralize the negative impact of «anti-Ukrainian» legislative norms on bilateral relations.